REMEDIASI KESALAHAN SISWA DALAM MENYELESAIKAN SOAL TEKANAN ZAT PADAT MENGGUNAKAN METODE FEEDBACK BERBANTUAN LEAFLET - Razali, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstrakThis study was aimed to know the effectiveness of feedback method using leaflet to remediate students’ mistakes in solving solid pressure in SMPN 23 Pontianak. This study was a quasi experimental design with nonequivalent control group design. The sample of this study consisted of 28 students of class VIII B as experiment class 1 and 30 students of class VIII E as experiment class 2. Tools of data collection were essay test amount to five questions that has been validating (level of validation 3.5 in moderate category) and test reliabilities (level of reliabilities 0.489 in moderate category). This study showed that the percentage of students’ mistakes of experiment class 1 was 52.8% and experiment class 2 was 52.9%. The lowering of students’ mistakes happened to 12.5% and 15.3%. Based on the result of U-Mann Whitney with 5% significant equal obtained -Zhitung< -Ztabel, that was 0.05 < 1.96 so Ho accepted. The result showed that there was no different of the number of students’ mistakes between the class that remediated by feedback method using leaflet and without leaflet. It was hoped that this research can be a reference to the educators in doing remediation.Keywords: Feedback Method, Students’ Mistakes, Leaflet, Solid Pressure